Frequency domain‐based configuration and power follow‐up control for power sources in a grid‐connected microgrid. (2nd October 2014) - Zheng, Lingwei; Liu, Shirong; Xie, Xiaogao
Summary: Usually, distributed generations with natural energies bring negative effects to the utility grid. Microgrid with various power sources is able to eliminate these negative effects. A frequency domain‐based method is proposed in this paper for configuration and control design of power sources in a grid‐connected microgrid. First, the power sources are configured based on their frequency spectrum features. After that, the frequency domain‐based power follow‐up control is applied to the power sources, and the power at the point of common couple (PCC) is regulated to follow up a desired power value. Detailed theoretical analysis of the frequency domain‐based method for configuration and power follow‐up control of power sources are presented. Finally, a microgrid in a campus with multiple power sources is designed based on the proposed configuration method and control method. Frequency domain analysis and experimental results show that the power at PCC can be regulated to a desired value, i.e. the disturbances to the grid caused by loads and renewable resources in microgrid are successfully suppressed. Copyright © 2014 John Wiley & Sons, Ltd.